Parental imprinting studied by allele-specific primer extension after PCR: paternal X chromosome-linked genes are transcribed prior to preferential paternal X chromosome inactivation. - Singer-Sam, J (1992)
The preferential inactivation of the paternal X chromosome in extraembryonic cells during early mouse development is an example of parental imprinting, but it has not been studied at the transcriptional level because standard methods of measuring RNA levels do not allow detection of allele-specific RNAs in individual early embryos. We sought to determine whether the paternal allele of the X chromosome-linked gene for 3-phosphoglycerate kinase 1 (Pgk-1), which is located very near the center of X chromosome inactivation, is transcribed prior to differentiation of extraembryonic lineages. Previous reports indicated that in heterozygous embryos there is a delay in the appearance of the phosphoglycerate kinase 1 allozyme encoded by the paternal X chromosome until 2 days after the appearance of the corresponding maternal allozyme. We report results obtained by use of a reverse transcription/PCR-based method which allows the quantitative measurement of allele-specific RNA. The assay is sensitive enough for the quantitative analysis in single embryos of allele-specific transcripts differing by only one nucleotide. We have used this assay to analyze mouse embryos heterozygous at the Pgk-1 and Hprt [hypoxanthine (guanine) phosphoribosyltransferase] loci, and we find that individual 8-cell and blastocyst embryos express both Hprt and Pgk-1 paternal transcripts, as do pooled 2- to 4-cell embryos. These results are discussed in view of the apparent temporal delay in paternal expression of the Pgk-1 gene at the enzyme level.